4(2a-3)-2(a-4)=3(a-3)-1

Simple and best practice solution for 4(2a-3)-2(a-4)=3(a-3)-1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(2a-3)-2(a-4)=3(a-3)-1 equation:


Simplifying
4(2a + -3) + -2(a + -4) = 3(a + -3) + -1

Reorder the terms:
4(-3 + 2a) + -2(a + -4) = 3(a + -3) + -1
(-3 * 4 + 2a * 4) + -2(a + -4) = 3(a + -3) + -1
(-12 + 8a) + -2(a + -4) = 3(a + -3) + -1

Reorder the terms:
-12 + 8a + -2(-4 + a) = 3(a + -3) + -1
-12 + 8a + (-4 * -2 + a * -2) = 3(a + -3) + -1
-12 + 8a + (8 + -2a) = 3(a + -3) + -1

Reorder the terms:
-12 + 8 + 8a + -2a = 3(a + -3) + -1

Combine like terms: -12 + 8 = -4
-4 + 8a + -2a = 3(a + -3) + -1

Combine like terms: 8a + -2a = 6a
-4 + 6a = 3(a + -3) + -1

Reorder the terms:
-4 + 6a = 3(-3 + a) + -1
-4 + 6a = (-3 * 3 + a * 3) + -1
-4 + 6a = (-9 + 3a) + -1

Reorder the terms:
-4 + 6a = -9 + -1 + 3a

Combine like terms: -9 + -1 = -10
-4 + 6a = -10 + 3a

Solving
-4 + 6a = -10 + 3a

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-3a' to each side of the equation.
-4 + 6a + -3a = -10 + 3a + -3a

Combine like terms: 6a + -3a = 3a
-4 + 3a = -10 + 3a + -3a

Combine like terms: 3a + -3a = 0
-4 + 3a = -10 + 0
-4 + 3a = -10

Add '4' to each side of the equation.
-4 + 4 + 3a = -10 + 4

Combine like terms: -4 + 4 = 0
0 + 3a = -10 + 4
3a = -10 + 4

Combine like terms: -10 + 4 = -6
3a = -6

Divide each side by '3'.
a = -2

Simplifying
a = -2

See similar equations:

| 3+4+x=1+6 | | 6(y-5)=z(10+3y) | | 5x+11y+1z=57.73 | | 15x+13=3x-19 | | X-5c=8 | | .75a+14=18 | | X-3/6=1 | | .75+14=18 | | -4=5m+6 | | -17e=-204 | | 2x-33=x+1 | | 15n^2-n-16=0 | | 75-n+10=60 | | 9n+5n=23 | | 50-n+20=38 | | 4x-8=144 | | 90+40+(6x+2)=180 | | 55-n+41=62 | | 8(36+r)r=12 | | 2y+2a-8y=5 | | 6xsquared+9x=0 | | 1-4r-5r=1 | | 0.4(60)= | | 48-n+10=34 | | 15c-7=53 | | 6xsquared+9=0 | | .9x-2.3x=3.8 | | 10-n+60=64 | | 16.2(-4.5x-3)=-85.05 | | -4v+23=5(v+1) | | ln(3x+3)=0 | | 3(x-1)+(x-6)= |

Equations solver categories